The Effect of Health Protocol Security Implementation, Employee Competence, and Service Quality toward MRT Transportation Customer Satisfaction during Covid-19 Pandemic - Freddy SP Hutabarat; TB.M.Rizki Indra Permana; Liana Patricia Masella (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
The aim of this study is to determine whether the application of health protocol security, employee competence, and service quality during the covid-19 pandemic could affect customer satisfaction toward MRT transportation. This research is included in descriptive quantitative. The sample is taken by total sampling technique with a total of 100 respondents who use MRT transportation. Data collection technique in this research uses questionnaire. Statistical analysis is carried out with the help of the Partial Least Squares Structured Equestrian Model (PLS-SEM) program. The results of this study are (1) the health protocol security (X1) has a significant positive effect toward customer satisfaction, (2) employee competence (X2) has a significant positive effect toward customer satisfaction, and (3) the quality of service (X3) has a significant positive effect on customer satisfaction. Therefore, it can be concluded that all the independent variables in this study have an effect on the related variables. From the results of this study, the researchers hope that in order to increase the satisfaction of MRT users, the MRT can improve the security of health protocols, employee competence, and service quality.